The First Wives Club - Rudin, Scott, 1958-; Wilson, Hugh, 1943-; Harling, Robert, 1951-; Midler, Bette; Hawn, Goldie; Keaton, Diane; Smith, Maggie, 1934-; Hedaya, Dan.; Pinchot, Bronson; Harden, Marcia Gay.; Garber, Victor; Goldsmith, Olivia; et al. (Hollywood, Calif. : Paramount Pictures, 1998)
Three mid-life Manhattanites have more than a longtime friendship in common. After years of helping their hubbies climb the corporate ladder of success, each has been dumped for a newer, curvier model. The trio is determined to turn their pain into gain. They come up with a cleverly devious plan to hit their exes where it really hurts--in the wallet!
For specific features see interactive menu.
Title from disc surface.
Based on the novel by Olivia Goldsmith.
Originally released as motion picture in 1996.
Director of photography, Donald Thorin; editor, John Bloom; music, Marc Shaiman.
Bette Midler, Goldie Hawn, Diane Keaton, Maggie Smith, Dan Hedaya, Bronson Pinchot, Marcia Gay Harden, Victor Garber.
Keywords: Divorced women -- Drama; Revenge -- Drama; Feature films; Comedy films; Film adaptations; Video recordings for the hearing impaired